Molecular Imaging of Cancer with Nanoparticle-Based Theranostic Probes. (19th June 2017) - Ma, Ying-Yu; Jin, Ke-Tao; Wang, Shi-Bing; Wang, Hui-Ju; Tong, Xiang-Min; Huang, Dong-Sheng; Mou, Xiao-Zhou
Abstract : Although advancements in medical technology supporting cancer diagnosis and treatment have improved survival, these technologies still have limitations. Recently, the application of noninvasive imaging for cancer diagnosis and therapy has become an indispensable component in clinical practice. However, current imaging contrasts and tracers, which are in widespread clinical use, have their intrinsic limitations and disadvantages. Nanotechnologies, which have improved in vivo detection and enhanced targeting efficiency for cancer, may overcome some of the limitations of cancer diagnosis and therapy. Theranostic nanoparticles have great potential as a therapeutic model, which possesses the ability of their nanoplatforms to load targeted molecule for both imaging and therapeutic functions. The resulting nanosystem will likely be critical with the growth of personalized medicine because of their diagnostic potential, effectiveness as a drug delivery vehicle, and ability to oversee patient response to therapy. In this review, we discuss the achievements of modern nanoparticles with the goal of accurate tumor imaging and effective treatment and discuss the future prospects.